Finding the optimal road routes between two locations in East Kuala Lumpur by using A* Algorithm based on GPS data / Ilina Syazwani Musa - Musa, Ilina Syazwani (2007)
The computation of the shortest path is an essential task in many network and transportation related analyses. The research efforts have been done over the years by the researchers around the world by using a number of different algorithms and different cases study. In this paper, we will use A* algorithm in road route in East Kuala Lumpur based on GPS data on the Garmin platform. It will compute the optimal road route between two locations within the area.